2019
DOI: 10.3390/app9235035
|View full text |Cite
|
Sign up to set email alerts
|

Ni3Se4@MoSe2 Composites for Hydrogen Evolution Reaction

Abstract: Transition metal dichalcogenides (TMDs) have been considered as one of the most promising electrocatalysts for the hydrogen evolution reaction (HER). Many studies have demonstrated the feasibility of significant HER performance improvement of TMDs by constructing composite materials with Ni-based compounds. In this work, we prepared Ni3Se4@MoSe2 composites as electrocatalysts for the HER by growing in situ MoSe2 on the surface of Ni3Se4 nanosheets. Electrochemical measurements revealed that Ni3Se4@MoSe2 nanohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The compositional ratio of Ni, Co, and S measured by the XPS (Table S4) was different from those by EDS (Figure S9 and Table S3) owing to the different analytic depths of the two instruments. As indicated in Figure 6B, the Ni 2p 3/2 spectrum of the Ni‐Co/CP electrode was divided into an Ni 0 peak at 852.3 eV, Ni 2+ peak at 855.7 eV, and Ni satellite peak at 861.4 eV 64‐68 . Conversely, for the Ni‐Co‐S/CP electrode, the Ni 0 peak vanished and the Ni 2+ peak shifted 0.3 eV to a higher binding energy, demonstrating the oxidized electronic structure of the Ni, compared with the Ni‐Co/CP case.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The compositional ratio of Ni, Co, and S measured by the XPS (Table S4) was different from those by EDS (Figure S9 and Table S3) owing to the different analytic depths of the two instruments. As indicated in Figure 6B, the Ni 2p 3/2 spectrum of the Ni‐Co/CP electrode was divided into an Ni 0 peak at 852.3 eV, Ni 2+ peak at 855.7 eV, and Ni satellite peak at 861.4 eV 64‐68 . Conversely, for the Ni‐Co‐S/CP electrode, the Ni 0 peak vanished and the Ni 2+ peak shifted 0.3 eV to a higher binding energy, demonstrating the oxidized electronic structure of the Ni, compared with the Ni‐Co/CP case.…”
Section: Resultsmentioning
confidence: 94%
“…As indicated in Figure 6B, the Ni 2p 3/2 spectrum of the Ni-Co/CP electrode was divided into an Ni 0 peak at 852.3 eV, Ni 2+ peak at 855.7 eV, and Ni satellite peak at 861.4 eV. [64][65][66][67][68] Conversely, for the Ni-Co-S/CP electrode, the Ni 0 peak vanished and the Ni 2+ peak shifted 0.3 eV to a higher binding energy, demonstrating the oxidized electronic structure of the Ni, compared with the Ni-Co/CP case. Similar behavior was also observed in the Co 2p 3/2 spectra for the Ni-Co/CP and Ni-Co-S/CP electrodes ( Figure 6C).…”
Section: Effect Of Ch 4 N 2 S Concentration In Deposition Electrolytementioning
confidence: 99%
“…In addition to synergistic metal doping on Ni x Se y -based electrocatalysts, the construction of the heterostructure on nickel selenide could also optimize the surface/interface electronic structure and facilitate intrinsic catalytic activity and electrical conductivity. Wang et al constructed NiSe 2 –Ni 2 P coupling heterostructures on NF, which confirmed that the heterojunction formation can significantly improve the water splitting activity of host material NiSe 2 , and DFT calculations were carried out to understand the influence of the heterogeneous interface on the significantly enhanced catalytic performance (Figure a-f) . Zhang et al prepared the three-dimensional substrate electrode CoSe 2 @NiSe 2 material for the first time, which maximizes the synergistic effect between CoSe 2 and NiSe 2 .…”
Section: Ni X Se Y -Based Electrocatalysts For Water Splittingmentioning
confidence: 99%
“…However, conventional strategies have been reported to construct the interfaces between MoSe 2 and nickel selenide in synthetic routes. One is to use one-step hydrothermal synthesis, which makes metal ions and selenium ions combine freely in solution. , The other is to synthesize MoSe 2 first and adopt the epitaxial growth method of nickel selenide in MoSe 2 surfaces. The two synthetic routes make the phase distribution uneven and the interface less. However, the more interfaces exposed to the catalyst, the larger and wider the lattice strain is.…”
Section: Introductionmentioning
confidence: 99%